Prevalence of visual impairment and severity of diabetic retinopathy in various ethnic groups in the UK - Gupta, Bhaskar (Cranfield University, 2011)
Diabetic Retinopathy (DR) is a leading cause of visual impairment (VI) in the working population. Minor ethnic groups are at increased risk of diabetes. Diabetic Retinopathy In Various Ethnic groups in the United Kingdom (DRIVE UK) is a cross-sectional study to estimate the prevalence of DR, VI and associated risk factors for sight threatening diabetic retinopathy (STDR) in Afro-Caribbeans (AC) and South Asians (SA) compared to Caucasians. People with diabetes in two regions in the United Kingdom who were screened and/or treated for DR from September 2008 to September 2009 were included in this study. VI and severe visual impairment (SVI) were defined as Snellen visual acuity of ≤ 6/18 and ≤ 6/60 respectively. DR was graded according to National Screening Committee (NSC) for diabetes guidelines UK. There were 57,144 people on the diabetic register, of which retinopathy data was available from 50,285 (88.1%) subjects (type 1 n=3,323, type 2 n=46,962). In type 1 and type 2 diabetes, any DR was detected in 53.1%, 39.5%, diabetic maculopathy in 13.1%, 8.4% and STDR in 9.91%, 4.0% of people respectively. STDR was significantly more prevalent in the SA (10.3%) and AC (11.5%) populations compared to Caucasians (5.5%). Overall VI was significantly higher in the ethnic minority population. A total of 7.5% (95% CI 7.3, 7.8) people with diabetes were not eligible for driving based on their visual acuity, 3.4% (95% CI 3.2, 3.5) were classified as VI and 0.4% (95% CI 0.33, 0.44) as SVI. Risk factors for STDR were found to include longer duration of diabetes and higher mean HbA1c. This study provides information that could be used to help develop future service frameworks and guidelines for local health bodies responsible for delivery of end userservices. The study also supports the need to explore the role of inflammatory, genetic and epigenetic factors as markers for ethnic differences in DR and potential treatment avenues for diabetic retinopathy.